(untitled) (Modern education and development, 2025)
В статье рассматривается подготовка учащихся и преподавателей к этичному и ответственному использованию искусственного интеллекта (ИИ). Освещаются ключевые этические вопросы, роль преподавателей, методология обучения и международный опыт. Анализируются вызовы и перспективы внедрения этических стандартов в образовательный процесс, направленных на формирование осознанного использования ИИ. The article examines the preparation of students and teachers for the ethical and responsible use of artificial intelligence (AI). It highlights key ethical issues, the role of educators, training methodologies, and international experiences. The challenges and prospects of implementing ethical standards in the educational process to promote the conscious use of AI are analyzed.